If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -22 + -3x = -2x + x + -3X Reorder the terms: -22 + -3x = -3X + -2x + x Combine like terms: -2x + x = -1x -22 + -3x = -3X + -1x Solving -22 + -3x = -3X + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. -22 + -3x + x = -3X + -1x + x Combine like terms: -3x + x = -2x -22 + -2x = -3X + -1x + x Combine like terms: -1x + x = 0 -22 + -2x = -3X + 0 -22 + -2x = -3X Add '22' to each side of the equation. -22 + 22 + -2x = 22 + -3X Combine like terms: -22 + 22 = 0 0 + -2x = 22 + -3X -2x = 22 + -3X Divide each side by '-2'. x = -11 + 1.5X Simplifying x = -11 + 1.5X
| -5=4x-3x | | 4w+5=5w-6 | | .5(2x+4)=3x-4 | | 4(8-x)=2x+16 | | -63+3y+8=2(5y-3)-7 | | 8n+11=10n-11 | | 2(x-5)=15x-4x | | x+(x*.0975)=4.21 | | .3x+1.4=4.2-.1x | | 4m+4=10m-62 | | -7/10m=-1324/24 | | 4+17n-3=9n+85-47 | | 100/900=85/x | | Y=-2x^3-2x^2+60x | | ax-2cx+4ay-8cy= | | 18-8-2=.5(18-2) | | -27+3*27=27+27 | | -u+106=240 | | c-3=2-3 | | 2-4-3-4=4 | | 267=158-u | | 2d+2=3d-4 | | Y=-1/4-4-5 | | 10-6*-3=2(-3-3) | | 27+9w=12w | | 2d+3=3d-4 | | 10-6x-3=2(-3-3) | | 5.2+1.2n=1.84 | | 10u=54+u | | 2(-2)-3+(-2)+1= | | 2x-20=3x+6 | | 0.5x+x=169 |